2013
DOI: 10.4103/0970-4388.112403
|View full text |Cite
|
Sign up to set email alerts
|

In vitro remineralization of enamel subsurface lesions and assessment of dentine tubule occlusion from NaF dentifrices with and without calcium

Abstract: Within the limitations of our study, sodium fluoride showed relatively greatest remineralizing and dentinal tubule occlusion property when compared with GC MI paste plus and Clinpro tooth crème.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 0 publications
2
19
1
2
Order By: Relevance
“…Although some studies shows some substances as gold stantards in occluded tubules, specially Sodium Potassium Phosphosilicate [1,13,15,23,24,26,31,32], in our research all dentifrices were able to occluded dentinal tubules without any statistical difference. It could be seen at SEM images and qualitative analyses.…”
Section: Mean (%) ± Sdcontrasting
confidence: 66%
See 1 more Smart Citation
“…Although some studies shows some substances as gold stantards in occluded tubules, specially Sodium Potassium Phosphosilicate [1,13,15,23,24,26,31,32], in our research all dentifrices were able to occluded dentinal tubules without any statistical difference. It could be seen at SEM images and qualitative analyses.…”
Section: Mean (%) ± Sdcontrasting
confidence: 66%
“…As fl uoride could affect the occluded of tubules as previous studies demonstrated [25,31], it was chose storage the samples in natural saliva from donors that have not using fl uoride dentifrices during the time of salive collection. This time was short to the point of not harming the donors.…”
Section: Mean (%) ± Sdmentioning
confidence: 99%
“…Though Biondi et al, Ozgul et al , Bakkal et al, and Pasini et al reported positive results after applying CPP‐APC pastes, its effectiveness as desensitizing and remineralizing agent has been questioned and long‐term clinical trials with large samples are needed to validate the results before its widespread recommendation.…”
Section: Discussionmentioning
confidence: 99%
“…Assim, cada tipo de lesão dentinária tem característi-cas clínicas próprias e procedimentos de controle diferentes a serem associados ao tratamento 12,[18][19][20] . Em lesões de abrasão, a atenção deve ser enfatizada para as orientações da técnica e da pressão utilizada na escovação, bem como para os tipos de escovas e de dentifrícios usados 28,30 . Apesar de não ser consenso, há autores que afirmam que a escova elétrica causa causa menor desgaste, pois realiza mínimna pressão na escovação.…”
Section: Discussionunclassified
“…Para o tratamento da hipersensibilidade, verifica-se também a utilização do fluoreto de sódio que, em contato com a dentina reage com o cálcio ionizado do fluido tubular, formando um precipitado de fluoreto de cálcio insolúvel responsável pela diminuição da condução hidráulica nos túbulos dentinários. Os dentifrícios com cálcio apresentam resultados mais efetivos na obliteração dos túbulos dentinários 28 . Contudo, observou-se que o efeito das soluções fluoretadas é de curta duração, além de serem necessárias várias aplicações para obtenção de um resultado significativo na redução da dor 13,15 .…”
Section: Tratamento Da Hsdcunclassified